Effect of the Ration Form on Productive Performance of Three Japanese Quail Breeds - waleed, Raghad Naseer (Journal of agricultural, environmental and veterinary sciences, 2020)
The study was carried out on (720) chicks of three strains of Japanese quail (desert, black and white) to investigate of effects the strain and shape of rations (crushed, granulated and crumbly) and by three treatments with four replicates for each strain during the growth period (1- 35 days), and 324 females of the same breeds. Three treatments with four replicates per breed during egg production (42- 101 days). The results showed significant differences (P≤0.05) of strain effects on body weight, weight gain, feed conversion coefficient-, carcass weight during the growth stage, and egg weight during the egg production stage. As for the effect of the diet, it was found that there were significant differences (P≤0.05) for Vivo weight characteristics, weight gain, feed conversion coefficient, carcass weight during the growth stage, egg weight and its mass, total eggs during the stage of egg production. While for the effect of the interaction between the strain and form of fodder showed the results significant differences (P≤0.05) in vivo weight and weight gain and feed conversion factor and carcass weight and net growth stage, crust ratio, egg weight, total egg number, total egg mass and albumin concentration during egg production.As for the economic calculations, the results showed that the desert quail breed got the best profit (Iraqi dinar/ kg live weight) during the growth phase, while the white quail breed got the best profit (Iraqi dinar/kg eggs) during the production phase of eggs. The best profit due to the effect of the form of the diet was the share of fodder grain during the growth and egg production. The best profit for the interaction of the strain and the form of the bush was the interaction of the desert quail strain with grain feed during the growth stage, and the interaction of the white quail strain with grain feed during the egg production.
Keywords: the strain of Japanese quail; ration; Mash; pellets and crumble